2021
DOI: 10.1002/pon.5755
|View full text |Cite
|
Sign up to set email alerts
|

Sexual satisfaction and sexual distress after cancer: The role of body image disruption, self‐compassion, sexual pain and relationship satisfaction

Abstract: Objective To identify variables that correlate with sexual satisfaction and sexual distress among adult cancer survivors, and how these differ, providing a basis from which approaches to intervention may be identified. This study examined four key variables: body image disruption, self‐compassion, relationship satisfaction and sexual pain, previously all linked to sexual quality of life. Methods A cross‐sectional survey was conducted online, with participants (n = 113) recruited via cancer charities, support g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…It may be that in an immediate way, compassionate behaviors represent a potent balm for relationships, with forgiveness and gratitude (within the relationship context) prompting individuals be more introspective and connected to their partner, which in turn facilitates individual sexual behaviors and well-being. More than just alleviating distress ( Santerre-Baillargeon et al, 2018 ; Michael et al, 2021 ), compassionate behaviors provide targeted and supportive emotional and relational comfort to the self ( Germer, 2009 ), which then encourages an accepting sexual environment ( Leavitt et al, 2021e ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be that in an immediate way, compassionate behaviors represent a potent balm for relationships, with forgiveness and gratitude (within the relationship context) prompting individuals be more introspective and connected to their partner, which in turn facilitates individual sexual behaviors and well-being. More than just alleviating distress ( Santerre-Baillargeon et al, 2018 ; Michael et al, 2021 ), compassionate behaviors provide targeted and supportive emotional and relational comfort to the self ( Germer, 2009 ), which then encourages an accepting sexual environment ( Leavitt et al, 2021e ).…”
Section: Discussionmentioning
confidence: 99%
“…Each relationally compassionate element discussed above can be connected to various aspects of sexual well-being. Though no research we know of has linked relational compassion and sexual well-being generally, some “sister” research has evaluated the role of self -compassion within circumstances of sexual distress and found that self-compassion is negatively associated with sexual distress, but not necessarily with sexual satisfaction ( Santerre-Baillargeon et al, 2018 ; Michael et al, 2021 ). Other studies found positive links between mindfulness and sexual well-being ( Leavitt et al, 2021c ) and compassion and to higher relationship quality generally ( McDonald et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For inter- and intrapersonal resources, the bivariate analyses of our study identified a positive correlation between factors such as social support, relationship satisfaction, and functioning levels including global quality of life, and the outcome of sexual satisfaction. Previous research among cancer survivors found that higher sexual satisfaction was significantly associated with higher relationship satisfaction 31 . Our correlation was relatively small and in regression analyses, we found no such effect.…”
Section: Discussionmentioning
confidence: 91%
“…anxiety, depression, low quality of life and low social support) [26][27][28][29][30] . With some exceptions 31,32 , less is known about the factors that are associated with sexual satisfaction in long-term cancer survivors with a cancer diagnosis across all entities.…”
mentioning
confidence: 99%
“…For that reason, sexual rehabilitation during cancer treatment should not focus just on coital frequency, but rather should include other aspects of human sexuality as a broader concept of psychosexual wellbeing [ 22 , 23 ]. It is of great importance that positive sexual self-schema might facilitate adjustment to new life after a cancer diagnosis [ 24 , 25 ], and body image disturbances correlate with sexual distress [ 26 ].…”
Section: Introductionmentioning
confidence: 99%